2016
DOI: 10.1589/jpts.28.1964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic knee osteoarthritis on flexion-relaxation phenomenon of the erector spinae in elderly females

Abstract: [Purpose] This study investigated the flexion-relaxation phenomenon of the erector spinae in elderly women with chronic knee osteoarthritis and determined whether the flexion-relaxation phenomenon can be used as a pain evaluation tool in such cases. [Subjects and Methods] Seventeen elderly females with chronic knee osteoarthritis and 13 healthy young females voluntarily participated in this study. They performed three postural positions in 15 s: trunk flexion, complete trunk flexion, and trunk extension, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…While harnessing the entire data base to systematize more definitive trends than is evident in the present snapshot of current research may be valuable, it is the author's belief that more efforts towards developing carefully construed biomechanical, radiological, molecular, biochemical, and neuromuscular oriented prospective studies of adequate duration are indicated to advance this line of inquiry, despite the increasing volume of reports. To verify or dispute hypothetical evidence based associations depicted in Figure 1 and expand upon trends depicted in Table 2, more prospective studies focusing on muscle co-activation effects [17], the role of eccentric as well as concentric forces on the emergence and progression of osteoarthritic joint disease [40], as well as the role of distant muscles [42,69], and the tendon-aponeurosis complex [46] are indicated [46,59]. In addition, delineating the role of muscle fat infiltration [33,81], muscle inflammation [25], and vitamin D [30] and its impact on muscle structure and function in the context of osteoarthritis may…”
Section: Implications and Conclusionmentioning
confidence: 98%
See 2 more Smart Citations
“…While harnessing the entire data base to systematize more definitive trends than is evident in the present snapshot of current research may be valuable, it is the author's belief that more efforts towards developing carefully construed biomechanical, radiological, molecular, biochemical, and neuromuscular oriented prospective studies of adequate duration are indicated to advance this line of inquiry, despite the increasing volume of reports. To verify or dispute hypothetical evidence based associations depicted in Figure 1 and expand upon trends depicted in Table 2, more prospective studies focusing on muscle co-activation effects [17], the role of eccentric as well as concentric forces on the emergence and progression of osteoarthritic joint disease [40], as well as the role of distant muscles [42,69], and the tendon-aponeurosis complex [46] are indicated [46,59]. In addition, delineating the role of muscle fat infiltration [33,81], muscle inflammation [25], and vitamin D [30] and its impact on muscle structure and function in the context of osteoarthritis may…”
Section: Implications and Conclusionmentioning
confidence: 98%
“…Not only are different disease stages studied, with different tools, and with dissimilar premises and aims, but the challenges in synthesizing data from morphological studies, [39,46], alongside electromyographic studies [eg. 19,53,59], muscle volume studies [36], plus studies examining the role of elevated skeletal muscle FoxO1 protein and reduced IL-15 protein expression and strength in people predominantly with knee osteoarthritis [26], remains immense.…”
Section: Gr Up Smmentioning
confidence: 99%
See 1 more Smart Citation